The Impact of the Israel - Hamas (Palestine) War on the Indonesian Economy - Yudha, Eka Mahatva; Widodo, Pujo; Sutanto, Rudy (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
This research investigates the impact of the Israel-Hamas conflict in Palestine on the Indonesian economy. By examining changes in international trade, foreign investment and commodity price fluctuations, this study provides an in-depth analysis of the influence of regional instability and geopolitical tensions. The study also considers the socio-political effects in Indonesia in response to the conflict. The results show that although Indonesia was not directly involved in the conflict, the country experienced significant economic impacts, particularly in terms of trade and investment. The findings provide important insights into how global geopolitical conflicts can affect emerging economies.